1993
DOI: 10.1302/0301-620x.75b5.8376431
|View full text |Cite
|
Sign up to set email alerts
|

Revision of failed open reduction of congenital dislocation of the hip

Abstract: We report a review of 33 hips (32 patients) which had required repeat open reduction for congenital dislocation of the hip. They were followed up for a mean of 76 months (36 to 132). Factors predisposing to failure of the initial open reduction were simultaneous femoral or pelvic osteotomy, inadequate inferior capsular release, and inadequate capsulorrhaphy. Avascular necrosis had developed in more than half the hips, usually before the final open reduction. At review, 11 of the hips (one-third) were in Severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 0 publications
2
44
1
2
Order By: Relevance
“…As in all the previous reports [1,3,5], the poor final clinical and radiographic results reflect the numerous procedures performed in these children to obtain a stable, concentric reduction, the most common complication being avascular necrosis. We suggest that technical failure-namely inadequate soft tissue release-is usually the cause for re-dislocation in unilateral dislocations.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…As in all the previous reports [1,3,5], the poor final clinical and radiographic results reflect the numerous procedures performed in these children to obtain a stable, concentric reduction, the most common complication being avascular necrosis. We suggest that technical failure-namely inadequate soft tissue release-is usually the cause for re-dislocation in unilateral dislocations.…”
Section: Discussionmentioning
confidence: 50%
“…Previous reports have highlighted the problems of management of this difficult problem [1,3,5,6]. We present our experience with 17 patients (18 hips) who had redislocation following open reduction for DDH, analyse the possible causes of failure and examine the outcome on both a clinical and radiological basis.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a stump of the ligamentum teres causing redislocation has also been found. This stresses the importance of complete removal of all obstacles to reduction including the need for complete release of the transverse acetabular ligament [4,[128][129][130] . Risk factors for failed open reduction were not thoroughly evaluated.…”
Section: Open Reduction and Hip Reconstructionmentioning
confidence: 99%
“…Ten studies [11,15,19,20,24,38,40,64,67,74] reported the age-specific occurrence of Grade I or greater osteonecrosis but not Grade II or greater osteonecrosis. One additional study [46] reported osteonecrosis occurrence by age at index open reduction but not by operative approach (medial versus anterior) and was excluded from the meta-analysis.…”
Section: Critical Reviewmentioning
confidence: 99%
“…Sufficient subject-level data were available to exclude the following ineligible cases: four dislocations of the hip secondary to neuromuscular or teratologic causes [15,67], 188 hips treated by open reduction with concomitant pelvic osteotomy [8,10,19,20,29,31,33,38,46,59,69,74,95,96], and 280 hips treated by other ineligible interventions [23,64,85,94]. Additionally, one study [13] included 12 hips treated by medial open reduction that at least partly overlapped with a more recently published article [49].…”
Section: Study Characteristicsmentioning
confidence: 99%